2008
DOI: 10.1016/s1472-6483(10)60218-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different cryopreservation protocols on the metaphase II spindle in human oocytes

Abstract: The aim of this study was to evaluate the impact of different cryopreservation protocols on the repolymerization of metaphase (M)II spindles in human oocytes. Fresh aspirated donor oocytes were cryopreserved 3-4 h after retrieval using four different protocols: slow freezing using 1.5 mol/l 1,2-propanediol (PROH) + 0.2 mol/l sucrose (n = 36); 1.5 mol/l PROH + 0.3 mol/l sucrose (n = 34); 1.5 mol/l PROH + 0.3 mol/l sucrose with Na(+) depleted-choline replaced media (n = 27), and vitrification by the Cryotip meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 49 publications
1
47
0
2
Order By: Relevance
“…Disagreement also exists on the entity and type of cell damage that the oocyte may suffer as a result of cryopreservation. For example, several lines of evidence have been reported for and against the hypothesis that the metaphase II (MII) spindle can be irreversibly disrupted by low temperature storage [8][9][10][11][12][13]. In effect, during the process of freezing-thawing (or vitrification-warming) the oocyte is exposed to a variety of physical and chemical conditions, such as low or suboptimal temperatures, formation of intracellular ice crystals (IIC), osmotic stress and replacement of intracellular water with cryoprotective agents (CPAs), that may endanger its mere survival [14].…”
Section: Introductionmentioning
confidence: 99%
“…Disagreement also exists on the entity and type of cell damage that the oocyte may suffer as a result of cryopreservation. For example, several lines of evidence have been reported for and against the hypothesis that the metaphase II (MII) spindle can be irreversibly disrupted by low temperature storage [8][9][10][11][12][13]. In effect, during the process of freezing-thawing (or vitrification-warming) the oocyte is exposed to a variety of physical and chemical conditions, such as low or suboptimal temperatures, formation of intracellular ice crystals (IIC), osmotic stress and replacement of intracellular water with cryoprotective agents (CPAs), that may endanger its mere survival [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, although depolymerization of the oocyte's meiotic spindle is known to occur, a number of studies have now shown that the spindle reforms in the majority of oocytes after thawing [24][25][26][27][28][29]. The advent of ICSI for insemination has overcome any concern regarding potential premature cortical granule reaction [11].…”
Section: Introductionmentioning
confidence: 99%
“…We assume that the slight lag described for VODE at day 3 might be due to delayed intra-cytoplasmic ultrastructure reorganization of the egg after warming. If so, selecting only optimal quality of eggs before vitrification can be discussed or more than a 2-h post-warming incubation may be applied before egg microinjection [18]. Although VODE displayed lower percentage of B3 blastocysts at embryo culture day 5, percentage of blastocysts available at embryo culture day 5 is equal in VODE and FODE.…”
Section: Discussionmentioning
confidence: 99%